A Novel SCN8A mutation in a case of early-onset infantile epileptic encephalopathy: A Case Report - Keshri, Swasti; Goel, Anil Kumar; Shah, Seema; Garg, Ankit Kumar (Acta Biomedica Atenei Parmensis, 2022)
SCN8A gene encodes sodium channel alpha subunit Nav1.6, and its mutation is associated with Early Infantile Epileptic Encephalopathy-13 (EIEE-13). The mean age of onset is 4-5 months. The phenotype of SCN8A mutation varies from benign epilepsy syndromes, movement disorder, intellectual disability to severe epileptic syndromes with different types of seizures. We hereby report a case of a one-year old female who had an onset of infantile spasms on the seventeenth day of life, which gradually progressed to focal, multifocal, GTCS, and epileptic encephalopathy by one year of age associated with global developmental delay and hypotonia. All metabolic workup, TMS, GCMS, and MRI brain were normal. EEG at 2.5 months was suggestive of epileptic discharge arising from the left frontal region, evolving into generalized discharges. Whole exome sequencing revealed a heterozygous mutation in the SCN8A gene at exon 16 (p.Val892Ala) suggestive of Early Infantile Epileptic Encephalopathy-13 (EIEE-13). This is a novel mutation in the SCN8A gene which has not been reported previously in the literature.